Association of PDCD1 and CTLA-4 Gene Expression with Clinicopathological Factors and Survival in Non–Small-Cell Lung Cancer. Issue 7 (July 2015) - Deng, Lei; Gyorffy, Balazs; Na, Feifei; Chen, Baoqing; Lan, Jie; Xue, Jianxin; Zhou, Lin; Lu, You
<x xml:space="preserve">Abstract</x> Introduction: Immune checkpoint blockade is being investigated in clinical trials and showed great potential in lung cancer. The prognostic roles of and clinicopathological factors associated with immune checkpoint gene expression, CTLA-4 and PDCD1 remain largely undefined, which encodes cytotoxic-lymphocyte antigen 4 (CTLA-4) and programmed cell death 1 (PD-1), respectively. Methods: We used a lung cancer database of 1715 patients measured by Affymetrix microarrays to analyze the association of gene expression with clinicopathological factors and survival. Hazard ratio (HR) and 95% confidence interval (CI) for overall survival (OS) were calculated. Cutoffs were determined by median across the entire database. Results: In 909 patients with histology information, significantly higher PDCD1 and CTLA-4 expression were found in squamous carcinoma than adenocarcinoma. In 848 patients with known smoking history, current/former smokers were found to have significantly elevated gene expression compared with nonsmokers. Significant higher expression of both genes were found in TNM stage II versus I. Higher expression of PDCD1 predicted worse OS in univariate analysis, but not in multivariate (HR: 1.22; 95% CI: 0.53–2.79). CTLA-4 was marginally significant in univariate analysis of the entire set (HR: 1.15; 95% CI: 0.99–1.34). In patients with information for multivariate analysis, higher expression of CTLA-4 was associated with worse OS (HR: 1.96; 95% CI: 1.18–3.31). Conclusions: In this study with large number of patients, PDCD1 and CTLA-4 expression is significantly higher in squamous carcinoma and current/former smokers. Higher expression of CTLA-4, but not PDCD1 predicts worse survival.